STUDI KELAYAKAN TEKNIS PELANTAR PENDARATAN IKAN DI DESA JARING HALUS KECAMATAN SECANGGANG KABUPATEN LANGKAT SUMATERA UTARA - Rosidah Hafni; Jonny Zain; Polaris Nasution (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
The research was conducted during of May 2016 in the village of Jaring Halus Village Secanggang District of North Sumatra. This study aims to determine the best location suitable for development to the fishing port from three long bench in location.The method used a survey method. By comparing its aspects such as physical aspects of technical and aspects of fisheries potential. The results of the analysis show that the port site selection based on a comparison of the three points of observation sites in Jaring Halus, it can be concluded that the location at long bench III village is the best location for construction of fishing ports with score 159,58 points for factor of physical and 83,65 points for factor of fisheries potential.Keywords : Long bench, technical feasibility, Jaring Halus village